Decoding submergence tolerance in Prunus persica: Integrated transcriptomic and metabolomic acclimations of antioxidant system, cell wall dynamics, and hormonal signaling - Muhammad Ateeq; Dongmei Zhang; Jinping Xiao; Huiqin Zhang; Xingyi Shen; Jian Meng; Jinzhi Yang; Shariq Mahmood Alam; Muhammad Mohsin Kaleem; Muhammad Abbas Khan; Kaijie Zhu; Guohuai Li; et al. (Horticulture Advances)
Abstract Low oxygen stress (hypoxia) induced by submergence significantly impairs respiration in fruit trees, leading to reduced yield and, in extreme cases, tree mortality. While extensive research has focused on the root responses of peach trees to waterlogging, the mechanisms underlying leaf responses to complete submergence remain poorly understood. In this study, both transcriptomic and metabolic approaches were employed to explore the differential submergence tolerance between two peach cultivars: 'Dongxi Xiaoxian' (DX), which exhibits tolerance, and 'Hujing Milu' (HM), which is sensitive. Compared to HM, DX leaves experienced less decline in leaf verdancy, chlorophyll, and carotenoid content under submergence. DX leaves also showed enhanced antioxidant activities of ROS scavengers and reduced levels of H2O2 and MDA, correlating with improved tolerance. Transcriptomic analysis revealed significant alterations in the expression of genes involved in photosynthesis, glycan biosynthesis, and α-linolenic acid metabolism between the two cultivars. Key metabolites, including sugars (sorbitol and sucrose), amino acids (phenylalanine and L-norvaline), cell wall polysaccharides (lignin and pectin), and plant hormones (jasmonic acid and salicylic acid), were identified as critical for DX's superior submergence tolerance. These findings elucidate the mechanisms of peach leaf tolerance to submergence, providing insights into potential strategies for genetic improvement aimed at enhancing hypoxia resistance in fruit trees.